User Experience of Intraoral Scanners in Dentistry: Transnational Questionnaire Study - Ahmad Al-Hassiny; Dániel Végh; Dorottya Bányai; Ádám Végh; Zoltán Géczi; Judit Borbély; Péter Hermann; Tamás Hegedüs (Elsevier, 2023)
ABSTRACT: Introduction: Intraoral scanners (IOS) are continuing to gain popularity in clinical dentistry, replacing the traditional impression-taking and related technology. Despite their increasing importance, there are few data on the utility and usage of IOS amongst dentists. This study investigates the user experience of IOS technology as well as the perceived quality of a variety of IOS used by dental clinicians worldwide. Methods: An online survey of 1072 dentists was conducted to elicit data on the number of individual IOS used, their accessibility, the maintenance fees, and the programmes used. The first part of the questionnaire included demographic data and related questions, whilst the second part focussed on the specific IOS used by the respondents and the satisfaction with their scanners. Results: We surveyed 1072 respondents from 109 different countries. More than three-quarters of the survey cohort (78.8%) use IOS in their daily work, whilst 21.17% do not. The average number of scanners owned by the respondents was 1.5 (±0.9), and in total, the cohort used 36 different types of IOS. More than one-third (38.6%) of the respondents used computer-aided design (CAD) software as well. As for the frequency of IOS usage, 51.5% used the system on a daily basis, 28.2% did so 2 to 3 times a week, and 10.0% did so once a week. Overall, the top 3 IOS used by the cohort were Medit i700 followed by wireless Medit i700 and Dentsply Sirona Primescan. Conclusions: This study describes, for the first time, the IOS user experience in an international cohort. More than 75% of the respondents used IOS on a daily basis in their practice, whilst Medit and Dentsply Sirona brands were the most popular scanners amongst the group. It appears that digital impression-taking technology is universal, and digital workflow in dentistry will continue to grow.